111k views
1 vote
ao wants to check that the expression 3(4x – 6) simplifies to 12x – 18. What is the value when 2 is substituted for x into both expressions?

1 Answer

5 votes

First, let's substitute 2 for x in the expression, 3(4x-6)

3(4(2)-6) = 3(8-6) = 3(2) = 6

  1. The operations within the parenthesis should be done first.
  2. Multiplication is next. 4*2 = 8
  3. Then subtraction. 8-6 = 2
  4. Finally, multiply once again. 3*2 =6

Next, let's substitute 2 for x in the expression, 12x-18

12(2)-18 = 24-18 = 6

  1. Multiplication comes first in the order of operations. 12*2 = 24
  2. Then, subtraction. 24-18 = 6

The value of both expressions when substituting x for 2 is 6.


User SilentGhost
by
6.1k points